PENGARUH PENERAPAN STRATEGI BELAJAR AKTIF TIPE QUESTIONS STUDENTS HAVE DISERTAI KUIS TERHADAP PEMAHAMAN KONSEP METEMATIS SISWA KELAS VIII SMPN 23 PADANG - Ulfiani, Martha; Mukhni, Mukhni; Fitri, Dewi Yuliana (STKIP PGRI Sumbar, 2013)
The background of research causes ofÂ students do not courage to question the teachers andÂ student lessÂ understanding of mathematical concepts. This study aims is to determine students math concept comprehension with Questions Students Have strategy and quiz better than math concept comprehension with conventional learning. The research is experimental by using Randomized Control Group Only Design. Population is students in the class VIII SMPN 23 Padang. The instrument used is examination with reliability 0,81. To test hypothesis used t-test one side with MINITAB, obtained P-Value 0,000 less than Î± = 0,05, so hypothesis received. In conclusion, students math concept comprehension with Questions Students Have strategy and quiz better than students math concept comprehension with conventional learning.